Seleção de modelos multiníveis para dados de avaliação educacional - Coelho, Fabiano Rodrigues (Universidade Federal de São Carlos, 2017)
When a dataset contains a hierarchical data structure, a possible approach is the multilevel regression modelling, which is justified by the significative amout of the data variability that can be explained by macro level processes. In this work, a selection of multilevel regression models for educational data is developed. This analysis is divided into two parts: variable selection and model selection. The latter is subdivided into two categories: classical and Bayesian modeling. Traditional criteria for model selection such as Lasso, AIC, BIC, and WAIC, among others are used in this study as an attempt to identify the factors influencing ninth grade students’ performance in Mathematics of elementary education in the State of São Paulo. Likewise, an investigation was conducted to evaluate the performance of each variable selection criteria and model selection methods applied to fitted models that will be mentioned throughout this work. It was possible to conclude that, under the frequentist approach, BIC is the most efficient, whereas under the bayesian approach, WAIC presented better results. Using Lasso under the frequentist approach, a decrease of 34% on the number of predictors was observed. Finally, we identified that the performance in Mathematics of students in the ninth year of elementary school in the state of São Paulo is most influenced by the following covariates: mother’s educational level, frequency of book reading, time spent with recreation in classroom, the fact of liking Math, school global performance in Mathematics, performance in Portuguese, school administrative dependence, gender, father’s educational degree, failures and age-grade distortion.
Selection of multilevel models for educational evaluation data
Keywords: Modelos multiníveis; Seleção de modelos; Critério de informação; Prova Brasil; Multilevel models; Model selection; Information criterion; Brazil exam - basic education assessment; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA